Threat, Efficacy and Message Framing in Consumer Healthcare - Nachiketas, N.; Sivakumaran, B.; Kalro, A.; Sharma, Piyush (Emerald Group Publishing Limited, 2017)
Purpose: The purpose of this paper is to empirically examine the interactive effects of message framing, perceived threat and efficacy appeals on attitudes/intentions towards consumer healthcare communications, particularly, cataract surgery. Design/methodology/approach: This paper develops two conceptual models dealing with threat, efficacy and framing and tests them with data collected from two field experiments. Findings: The results reveal that high efficacy messages in combination with high threat or loss-framed messages have a significant positive influence on consumer attitudes and intentions in the consumer healthcare arena. Practical implications: The findings have managerial value and public policy implications for healthcare officials in developing effective communications material. Specifically, this paper recommends that high threat, high efficacy and loss-framed efficacy messages be used. Originality/value: This research extends previous work by demonstrating the effectiveness of threat appeals and framing on consumer attitudes and intentions to undergo cataract surgery. It also demonstrates the use of communication models in the healthcare domain.